The relationship between self-compassion and mobile phone addiction in university students: a chain mediation model - Jingyu Qiang; Ying Jin; Yuqi Li; Cheng Xu (Frontiers in Psychiatry)
BackgroundCurrently, the uncertainty and high pressure of the social environment, as well as the popularity of the Internet and mobile phones, have made mobile phone addiction a prevalent phenomenon among university students. This study explored the relationship between self-compassion and mobile phone addiction in university students and the mediating effects of negative attention bias and self-regulatory fatigue.MethodsThe study used convenience sampling to recruit 800 Chinese university students to complete the Chinese version of the Self-Compassion Scale, the Negative Attention Bias Scale, the Self-Regulatory Fatigue Scale, and the Mobile Phone Addiction Scale. SPSS 24.0 and the Process 3.4 macro program were employed to generate the descriptive statistics and conduct the correlation analyses and mediating effect tests on the data.ResultsThe analyses revealed that self-compassion negatively predicted mobile phone addiction. Negative attention bias and self-regulatory fatigue individually mediated the effect of self-compassion on mobile phone addiction. Negative attention bias and self-regulatory fatigue also exhibited a chain mediation effect.ConclusionsThe results of the study, from the perspective of self-compassion, have theoretical and practical implications for how to intervene in the mobile phone addiction of university students as well as to protect their physical and mental health.